ОВОЛОДІННЯ МЕТОДИЧНИМИ ПРИЙОМАМИ ОРГАНІЗАЦІЇ СПІЛЬНОЇ НАВЧАЛЬНОЇ ДІЯЛЬНОСТІ УЧНІВ - ОДИН З НАПРЯМКІВ ПРОФЕСІЙНОЇ ПІДГОТОВКИ МАЙБУТНІХ УЧИТЕЛІВ МУЗИКИ (Педагогіка вищої та середньої школи, 2022)
The traditional and other methodical techniques of effective nitftini. iifmn of educational activities of pupils at the music lesson at  school, analyzed in the article. Gaining the experience of using these twchniques improves the professional Teachers Training activities of the future specialists.